3D MRI-based multicomponent thin layer structure only plaque models for atherosclerotic plaques. Issue 13 (6th September 2016) - Huang, Xueying; Yang, Chun; Zheng, Jie; Bach, Richard; Muccigrosso, David; Woodard, Pamela K.; Tang, Dalin
Abstract: MRI-based fluid-structure interactions (FSI) models for atherosclerotic plaques have been developed to perform mechanical analysis to investigate the association of plaque wall stress (PWS) with cardiovascular disease. However, the time consuming 3D FSI model construction process is a great hinder for its clinical implementations. In this study, a 3D thin-layer structure only (TLS) plaque model was proposed as an approximation with much less computational cost to 3D FSI models for better clinical implementation potential. 192 TLS models were constructed based on 192 ex vivo MRI Images of 12 human coronary atherosclerotic plaques. Plaque stresses were extracted from all lumen nodal points. The maximum value of Plaque wall stress (MPWS) and average value of plaque wall stress (APWS) of each slice were used to compare with those from corresponding FSI models. The relative errors for MPWS and APWS were 9.76% and 9.89%, respectively. Both MPWS and APWS values obtained from TLS models showed very good correlation with those from 3D FSI models. Correlation results from TLS models were in consistent with FSI models. Our results indicated that the proposed 3D TLS plaque models may be used as a good approximation to 3D FSI models with much less computational cost. With further validation, 3D TLS models may be possibly used to replace FSI models to save time and perform mechanical analysis for atherosclerotic plaques for clinical implementation.